2016
DOI: 10.1007/s13277-016-5078-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of p21 gene C98A polymorphism on development of uterine leiomyoma in southeast Iranian women

Abstract: Uterine leiomyoma (UL) is a monoclonal tumor which arises from uninhibited proliferation of a single myometrial cell; therefore, the imbalance in cell cycle regulation could be a key event in its development. In the present study, we aimed to assess the association of p21 gene polymorphisms and UL. Genomic DNA was extracted from blood samples of 154 women with UL and 197 age-, BMI-, and ethnically matched controls. p21 C98A (rs1801270) and C70T (rs1059234) polymorphism genotypes were determined by polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…Growth factors may typically stimulate the angiogenesis of leiomyoma cells as compared with adjacent normal cells (Boehm et al, 1990;Di Lieto et al, 2005). Numerous investigations have revealed that both chromosome abnormalities in UL patients as well as genetic factors play key roles in UL pathogenesis in different countries, such as Iran (Gan et al, 2015;Salimi et al, 2015;Yaghmaei et al, 2015;Salimi et al, 2016). It is believed that ACE activity may be related to tumor growth and ACE inhibitors as well as angiotensin receptor blockers, thereby contributing to the suppression of tumor growth.…”
Section: Association Of Ace I/d and Agtr1 A1166c Gene Polymorphisms Amentioning
confidence: 99%
“…Growth factors may typically stimulate the angiogenesis of leiomyoma cells as compared with adjacent normal cells (Boehm et al, 1990;Di Lieto et al, 2005). Numerous investigations have revealed that both chromosome abnormalities in UL patients as well as genetic factors play key roles in UL pathogenesis in different countries, such as Iran (Gan et al, 2015;Salimi et al, 2015;Yaghmaei et al, 2015;Salimi et al, 2016). It is believed that ACE activity may be related to tumor growth and ACE inhibitors as well as angiotensin receptor blockers, thereby contributing to the suppression of tumor growth.…”
Section: Association Of Ace I/d and Agtr1 A1166c Gene Polymorphisms Amentioning
confidence: 99%
“…In addition, rs1059234 (C70T) is another P21 polymorphism, which is located downstream the stop codon in the 3′-untranslated region. This site is involved in cell proliferation, differentiation, and tumor suppression [14]. Several studies have indicated both genes and apoptotic pathways are important in the regulation on PE [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we observed no significant association between rs1059234 and rs1801270 polymorphisms of P21 gene and PTC risk. However, the association between these polymorphisms, risk of squamous cell carcinoma, 36 sporadic colorectal cancer, 37 cervical cancer, 34 prostate cancer, 38 uterine leiomyoma, 24 and Gastrointestinal Tract Tumor 39 has been reported previously. We also found no significant association between P21 polymorphisms (rs1059234 and rs1801270) and pathological and clinical characteristics of PTC.…”
Section: Discussionmentioning
confidence: 92%
“…For genotyping of studied polymorphisms, the polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) was performed. The primer's sequence, PCR condition, and restriction enzyme used are presented in previous publications …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation